The pathogenesis of extraintestinal manifestations: implications for IBD research, diagnosis, and therapy - Hedin, Charlotte; Vavricka, S. R.; Stagg, A. J.; Schoepfer, A.; Raine, T.; Puig, L.; Pleyer, U.; Navarini, A.; van der Meulen-de Jong, A. E.; Maul, J.; Katsanos, K.; Kagramanova, A.; et al. (Journal of Crohn's and Colitis, 2019)
Abstract. This article reports on the sixth scientific workshop of the European Crohn’s and Colitis Organisation [ECCO] on the pathogenesis of extraintestinal
Gesehen am 12.03.2020